Microbial Contamination Assessment of Ice Cubes Around Prasetiya Mulya University - Elfriede, Dwining Putri; Arinata, Kadek Wika (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Indonesia's tropical climate encourages its people to consume cold beverages as a way to stay refreshed. One of the main components of cold beverages is ice. The quality and hygiene of ice used by vendors usually neglect the quality of ice production and handling, posing potential health risk. This study aims to evaluate the safety of ice sold by vendors around Prasetiya Mulya University. Ice cube samples were collected from seven vendors using a plastic cup and taken directly to the laboratory. The study employs both qualitative and quantitative approaches. Qualitative data were obtained through interviews with employees or business owners to understand vendor characteristics and hygiene practices during operations. Quantitative data include three main tests: Total Plate Count (TPC), Most Probable Number (MPN), and environmental monitoring. The results provide evidence-based insights to support public health initiatives and promote the sustainability of informal food businesses around Prasetiya Mulya University. The study revealed that all ice samples from seven locations did not meet the microbiological standards by SNI 3839:2019. All samples had microorganism counts greater than 10² CFU/mL, and estimated coliform bacteria counts ranged from 23 to ≥2400 MPN/100 mL. The confirmation of Escherichia coli presence in four out of seven samples, indicates fecal contamination. Sanitation evaluations using EB petrifilm also showed the ineffectiveness of ice scoop cleaning at several locations. These findings highlight the urgent need for improved hygiene practices among vendors. They require regular food safety training, enforcement of regulatory standards, and sourcing ice from certified suppliers.